Generalized impedance function simulator using voltage differencing buffered amplifiers (VDBAs) - Mongkolwai, Pratya; Tangsrirat, Worapong (My University, 2016)
A circuit topology for simulating grounded inductor, capacitance multiplier and frequency-dependent negative resistor (FDNR) depending on the passive component choice is presented. The presented general impedance function simulator employs two voltage differenclng buffered amplifiers (VDBAs) and three various passive components. The realized equivalent impedance values can be tuned electronically via the transconductance gains of the VDBAS. The simulator does not need any component matching constraints, and also exhibits low active and passive sensitivities. To verify the theory and to exhibit the circuit performance, computer simulation results using PSPICE are provided.
Keywords: Electronically tunable; Immittance function; Impedance simulator; Voltage differencing buffered amplifier (VDBA)